A ESCRITA DE SI NA AUTORIA DO ROMANCE A MANTA DO SOLDADO, DE LÍDIA JORGE - Scheifer, Paola (2012)
This study has as central theme the self-writing process in authorship of A manta do Soldado (2003), by Lídia Jorge, a Portuguese writer. This novel was first published in 1998 with another title, O vale da paixão, and it presents an author construction as well as she build the narrative we read. Thus, when we analyze how the authorial speech is built we realize the narrator shows her human need to narrate. The first goal of this research is evidence how the Walter’s daughter’s speechis made and this analysis is based on Michel Foucault’s theoretical discussions (1988) which investigate the sacrament of confession as a subjective way resulted by a deep self-examination. The second goal is to realize how is the means narrator disposes to write, trying to study it through Foucault’s theoretical supports (2002): hypomnemata and correspondence. These supports are part of narrator’s writing, considering them as a way of self-reflection. For this, it was punctuated the narrator’s registrations to observe the implication of Walter’s daughter, that is, the way of relation between her and her writing. From this, there’s the desire to build the Walter’s presence, by collected speeches. These registrations reveal the narrator as a subject in so far as they talk about Walter and compose her authorial speech that purpose narratives which are inserted in novel’s architecture, by the narrator. It’s arrived in a conception of how narrator self-constitutes her identity through writing, which places her, by Walter Dias, into narrative center. In an ambiguous speech, the writing revels, like the birds drawn by Walter, a possibility of transcendence, never permanent, achieved through art.